Concordance of MRI lesions and EEG focal slowing in children with nonsyndromic epilepsy. Issue 3 (29th January 2013) - Noh, Byoungho H.; Berg, Anne T.; Nordli, Douglas R.
Summary Purpose To investigate the significance of electroencephalography (EEG) focal slowing in children with epilepsy and to determine the correlation between focal slowing and focal lesions on brain magnetic resonance imaging (MRI). Methods We reviewed 5, 149 EEG and 22, 543 MRI reports for children who visited our institution from 2000 to 2010. Patients with nonsyndromic epilepsy (n = 253) were divided into groups with: focal slowing without any interictal epileptiform discharge (IED) (group 1); focal IEDs without focal slowing (group 2); focal slowing and focal IED (group 3); and normal findings (group 4). Focal slowing and MRI lesions were categorized by location, side, and depth. Key Findings We found MRI abnormalities in 59% of subjects in group 1, 56% in group 2, 74% in group 3, and 27% in group 4 (p < 0.0001). Cortical malformation (CM) was the most common pathology in groups with focal slowing. Focal slowing often correlated with the laterality of the MRI lesion (61–70%), but the location was concordant in only 40%. The associated lesions rarely were exclusively confined to the centrum semiovale (18%). Significance Focal slowing in children with epilepsy is highly associated with focal structural lesions on MRI, most commonly CM, and usually involves multiple layers. Focal slowing, as well as focal interictal epileptiform activity, is an important and useful EEG indicator of a brain structural abnormality in children with nonsyndromic epilepsy.